Keabsahan Hukum Tanda Tangan Elektronik pada Akta Notaris - Amanda apriyola; Donny Marbun; Emyllya Ayu Lestari; Putri Sari Dewi; Tiara Harlia (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The development of information technology has encouraged the use of electronic signatures in various transactions, including notarial deeds. However, their use raises legal issues regarding validity and evidentiary power. This study aims to analyze the legal validity of electronic signatures in notarial deeds and their implications. The results show that although recognized under positive law, electronic signatures cannot fully replace conventional signatures in authentic deeds. Therefore, regulatory harmonization is necessary to ensure legal certainty and protection.